Use of cone beam computed tomography for studying temporomandibular joint morphology - Lukšić, Ivan, stomatolog (Array, 2020)
The aim of the present study was to investigate morphology of temporomandibular joint using cone beam computer tomography. Study included 45 adults (32 females and 13 males). Articular eminence inclination, glenoid fossa width, glenoid fossa depth, condylar mediolateral distance, condylar anteroposterior distance and condylar type were determined for each temporomandibular joint. Since independent samples t-test did not show significant differences between left and right sides for all of observed parameters (p≥0.05), left and right side values were treated as one sample. The determined glenoid fossa depth was 7.11±2.23, glenoid fossa width 19.22±2.58, condylar anteroposterior distance 7.54±1.59, condylar mediolateral distance 17.95±2.81 and articular eminence inclination was 34.59±7.35 degrees. Most of condyles were classified as convex type (32.5%), followed by flattened (23.8%), rounded (11.3%) and angled (10%). Undefined (other type) were classified 22.5% of condyles. Cone beam computer tomography measurements of temporomandibular joint bone structures in present study showed similarities to most of previous research (with different populations studied). Still, the prevalence of different condylar types differs from those obtained by most of previous studies. Interindividual differences in temporomandibular joint morphology are expected.